THE EFFECT OF THE CULTURALLY RESPONSIVE TEACHING (CRT) APPROACH ON THE LEARNING MOTIVATION OF THIRD-GRADE STUDENTS IN ELEMENTARY SCHOOL - Celsi Andini; Nela Rofisian; Isna Rahmawati (Universitas Islam Negeri Mataram, 2026)
This study aims to determine the effect of the Culturally Responsive Teaching approach on learning motivation in the IPAS subject for third-grade students at SDN Banjarharjo. This is a quantitative study using a quasi-experimental design. The sample for this study consists of the third-grade class at SDN Banjarharjo as the experimental group, comprising 13 students, and SDN Menthel 2 as the control group. The control class is the class that did not receive the Culturally Responsive Teaching approach, while the experimental class received the treatment using the Culturally Responsive Teaching approach. The results of this study, based on analysis using SPSS version 26.0, showed a significant result where the hypothesis test using an independent samples t-test indicated that the calculated t-value of 0.485 was greater than the critical t-value of 0.484. These results indicate that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning there is a significant difference between the pre-intervention and post-intervention periods. Thus, it can be concluded that the implementation of the Culturally Responsive Teaching approach at Banjarharjo State Elementary School in the 2025/2026 academic year has a significant effect.